Mergers And Acquisitions In Islamic Banking Sector: An Empirical Analysis On Size Effect, Market Structure, And Operational Performance - Fauzias Mat Nor; Junaidah Abu Seman; Nur Ainna Ramli; Ahmad Fadly Nurullah Rasedee; Nazim Ullah (inderscience publisher, 2024)
Non-Indexed Publication